Analysis of the Mentoring Program on the development of Customer Business at Bank ABC: The Role of Facilitator Assistants at Rejoso Branch - Prahesty, Risti Farida Aprilia; Puspasari, Ismayantika Dyah (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this research is to analyze the role of facilitators on the Bestee Program in the business development of ABC Bank customers in MMS Rejoso and analyze the Bestee Program in supporting the business development of ABC Bank customers in the MMS Rejoso area.Design/Methode/Approach : This research uses a qualitative approach method, where to collect data through observation, documentation, and interviews in 5 ABC bank customers who have Micro, Small and Medium Enterprises and these customers were selected to take part in this bestee program.Research Finding : Bestee Program. This program involves student interns as accompanying facilitators and ABC bank customers as Micro, Small and Medium Enterprises who are participants in the mentoring program. Mentoring is carried out in 4 sessions (months), each session is divided into 4 meetings, namely introduction, teaching material, practice, and closing. The ABC bank mentoring program has had a significant positive impact, Micro, Small and Medium Enterprises have experienced an increase in product marketing through online platforms, increasing the competitiveness of their business. ABC bank's Bestee program has proven to be a strategic step in improving women's empowerment. Women empowerment through mentoring is very effective in improving the performance of Micro, Small and Medium Enterprises in Indonesia. By presenting mentoring that focuses on critical aspects, this program is able to create a real positive impact on the development of the local economy.Theoretical contribution/Originality : This research is expected to be able to add information on knowledge and skills for ABC bank customers who have Micro, Small and Medium Enterprises, so that after the customer gets the knowledge and skills taught by the facilitator during the business shelter, it can bring changes in the customer's Micro, Small and Medium Enterprises so that the customer's Micro, Small and Medium Enterprises experience development and improvement.Practitionel/Policy implication : Micro, Small and Medium Enterprises still face various challenges in terms of business management, technology utilization, and limited market access and for some people, the role of women is often underestimated due to patriarchal culture, which causes women's empowerment to be needed. With the “Bestee” program implemented by PT Bank ABC Tbk, it is possible to optimize the empowerment of women and the development of Mikto Small and Medium Enterprises through mentoring female customers or business women by providing comprehensive support in facing these challenges. Mentoring activities are carried out in MMS Talang, Rejoso District, Nganjuk Regency, an area with great potential for Micro, Small and Medium Enterprises but still faces obstacles in optimizing their potential. So for ABC bank customers, it is hoped that this research will be able to provide information, input and suggestions to ABC bank Micro, Small and Medium Enterprises customers in the form of suggestions and input related to the “Bestee Program” provided by ABC bank as a customer facility for business changes and developments that have a positive impact. For readers, this research is expected to be able to make references and effective mentoring models, this research provides an overview of the role of assisting facilitators in encouraging the success of customer businesses so that readers can learn the data used and how the model is used.Research limitation : The limitation of this research is in the scope of location because this research focuses on one area, namely at MMS Rejoso, Nganjuk Regency, so the results may not fully represent the implementation of the findings in all MMS or branches of ABC bank.